Psychological aspects of the interrogation tactics of an accused - Polák, Peter; Kubík, Ondrej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The contribution’s core content consists of an analysis of the general principles of the psychological approach to the interrogation of criminal accused, as well as an explanation of possible styles of conducting such interrogations.

Podstawową treścią merytoryczną artykułu jest analiza ogólnych zasad psychologicznego podejścia do przesłuchiwania oskarżonego, a także wyjaśnienia możliwych stylów prowadzenia takich przesłuchań.
Keywords: psychological aspects of the interrogation of an accused; psychological principles of conducting an interrogation; style of conducting an interrogation; psychologiczne aspekty przesłuchania oskarżonego; psychologiczne zasady prowadzenia przesłuchania; styl przeprowadzania przesłuchania